Temporal aspects of the VO2 response at the power output associated with VO2peak in well trained cyclists - Implications for interval training prescription übersetzter Titel (DE) - Laursen, P. B.; Shing, C. M.; Jenkins, D. G. (Research Quarterly for Exercise and Sport, 2004)
The power output achieved at peak oxygen consumption (VO2peak) and the time this power can be maintained (i.e., Tmax) have been used in prescribing high-intensity interval training. In this context, the present study examined temporal aspects of the VO2 response to exercise at the cycling power that output well trained cyclists achieve their VO2peak (i.e., Pmax). Following a progressive exercise test to determine VO2peak, 43 well trained male cyclists (M age = 25 years, SD = 6; M mass = 75 kg, SD = 7; M VO2peak = 64.8 ml×kg-1×min-1, SD = 5.2) performed two Tmax tests 1 week apart. Values expressed for each participant are means and standard deviations of these two tests. Participants achieved a mean VO2peak during the Tmax test after 176 s (SD = 40; M = 74% of Tmax, SD = 12) and maintained it for 66 s (SD = 39; M = 26% of Tmax, SD = 12). Additionally, they obtained mean 95% of VO2peak after 147 s (SD = 31; M = 62% of Tmax, SD = 8) and maintained it for 95 s (SD = 38; M = 38 % of Tmax, SD = 8). These results suggest that 60-70% of Tmax is an appropriate exercise duration for a population of well trained cyclists to attain VO2peak during exercise at Pmax. However, due to intraparticipant variability in the temporal aspects of the VO2 response to exercise at Pmax, future research is needed to examine whether individual high-intensity interval training programs for well trained endurance athletes might best be prescribed according to an athlete`s individual VO2 response to exercise at Pmax.